2021
DOI: 10.1007/s12022-021-09666-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology of Non-familial Follicular Epithelial–Derived Thyroid Cancer in Adults: From RAS/BRAF-like Tumor Designations to Molecular Risk Stratification

Abstract: This review addresses the impact of molecular alterations on the diagnosis and prognosis of differentiated thyroid carcinoma (DTC), including papillary, follicular, and well-differentiated carcinoma NOS, as well as oncocytic neoplasms. The molecular characterization of DTC is based upon the well-established dichotomy of BRAF-like and RAS-like designations, together with a remaining third group, less homogeneous, composed of non-BRAF-/non-RAS-like tumors. The role of BRAF V600E mutation in risk stratification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 161 publications
(243 reference statements)
1
19
0
Order By: Relevance
“…The analysis of gene expression profiles confirmed the BRAF- and RAS-like molecular subtypes previously identified by TGCA and distinguished a third molecular subtype defined as Non-BRAF-Non-RAS (NBNR), comprising FA and miFTC [ 133 ]. At present, however, classification of DTC into 3 molecular groups does not seem to improve the prognostic stratification of patients [ 134 ]. Recently, using information on the PTC patients’ cohort available in the TCGA data portal, we sought to verify whether DFI prediction, provided by clinicopathological parameters such as lymph node metastasis or age could be improved by molecular variables such as number of total non-silent mutations, number of CpGT mutations, BRAF-RAF score, ERK score, miRNA and RPPA clusters, ploidy, and TDS [ 11 , 83 , 135 , 136 ].…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of gene expression profiles confirmed the BRAF- and RAS-like molecular subtypes previously identified by TGCA and distinguished a third molecular subtype defined as Non-BRAF-Non-RAS (NBNR), comprising FA and miFTC [ 133 ]. At present, however, classification of DTC into 3 molecular groups does not seem to improve the prognostic stratification of patients [ 134 ]. Recently, using information on the PTC patients’ cohort available in the TCGA data portal, we sought to verify whether DFI prediction, provided by clinicopathological parameters such as lymph node metastasis or age could be improved by molecular variables such as number of total non-silent mutations, number of CpGT mutations, BRAF-RAF score, ERK score, miRNA and RPPA clusters, ploidy, and TDS [ 11 , 83 , 135 , 136 ].…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…The BRAF V600E mutation is the most prevalent genetic alteration (up to 80%) found in PTC tissues [ 11 ]. However, whether it could represent a reliable prognostic marker is highly debated [ 134 ]. Several studies reported an association between BRAF V600E mutation and PTC recurrences, presence of lymph node metastasis, advanced tumor stage and worse prognosis [ 137 , 138 , 139 , 140 , 141 , 142 , 143 ].…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…Hürthle cell carcinoma is considered a variant of follicular carcinoma [8]. Classification of the different subtypes of TC is outside the scope of this review and the reader is referred to expert reviews on this topic (e.g., [9][10][11]). The origins of the tumors are either the epithelial cells of the thyroid follicles (in PTC, FTC, and ATC) or the parafollicular cells, which produce the hormone calcitonin (in MTC).…”
Section: Thyroid Carcinomamentioning
confidence: 99%
“…The author focuses on two debates and possible explanations in this commentary: (1) why the prevalence of BRAFV600E mutation was high (50-90%) in Asian papillary thyroid carcinoma (PTC) patient cohorts but low (35-50%) in most Western PTC cohorts [2], and (2) why the BRAFV600E gene test identifies high-risk PTCs in Western patients [3][4][5][6], but the test results were not reproducible in most Asian patients [7][8][9][10][11][12][13]. Conflicts between different studies stem from a variety of reasons, including patient selection, different histological types included in the analysis, different methods applied for BRAFV600E testing, and epidemiological factors [2,6,[14][15][16]. The author believes it was due in significant part to an inconsistent diagnostic threshold of malignancy for including patient selection, different histological types included in the analysis, different methods applied for BRAFV600E testing, and epidemiological factors [2,6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%